2022
DOI: 10.3389/fbioe.2022.932936
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of CRISPR-Cas9 combined organoid model in the study of congenital nervous system malformations

Abstract: In the past 10 years, gene-editing and organoid culture have completely changed the process of biology. Congenital nervous system malformations are difficult to study due to their polygenic pathogenicity, the complexity of cellular and neural regions of the brain, and the dysregulation of specific neurodevelopmental processes in humans. Therefore, the combined application of CRISPR-Cas9 in organoid models may provide a technical platform for studying organ development and congenital diseases. Here, we first su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Recently, genome engineering such as CRISPR/Cas9 has been rapidly developed and applied to organoids. The combination of this technology with organoids could create new conditions for the study of organ development and the treatment of congenital diseases [ 99 ]. One of its advantages is the ability to facilitate the modelling of human cell-type diseases, like Mari Nakamura et al [ 100 ], who generated iPSC from patients and used CRISPR/Cas9 to insert MAPT genes to form frontotemporal family dementia (FTD) model and found that mutant tau proteins exhibited abnormalities such as reduced levels of phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genome engineering such as CRISPR/Cas9 has been rapidly developed and applied to organoids. The combination of this technology with organoids could create new conditions for the study of organ development and the treatment of congenital diseases [ 99 ]. One of its advantages is the ability to facilitate the modelling of human cell-type diseases, like Mari Nakamura et al [ 100 ], who generated iPSC from patients and used CRISPR/Cas9 to insert MAPT genes to form frontotemporal family dementia (FTD) model and found that mutant tau proteins exhibited abnormalities such as reduced levels of phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Bendriem et al used genome editing to knock out the gene Occludin (OCLN) in mouse and human models. OCLN KO resulted in early neuronal differentiation disorder, the slow self-renewal of progenitor cells and increased apoptosis in mice, whereas the human neural progenitor cells were seriously affected [56][57][58]. Leigh syndrome (LS) is another hereditary progressive neurodegenerative disease that leads to subacute necrotizing encephalomyelitis [56,57].…”
Section: Cutting-edge Technologies For Genetic Modifications Of Ipscs...mentioning
confidence: 99%
“…OCLN KO resulted in early neuronal differentiation disorder, the slow self-renewal of progenitor cells and increased apoptosis in mice, whereas the human neural progenitor cells were seriously affected [56][57][58]. Leigh syndrome (LS) is another hereditary progressive neurodegenerative disease that leads to subacute necrotizing encephalomyelitis [56,57]. Cell models of LS have been generated by using iPSCs from LS patients with a mutation in the gene for surfeit locus protein 1 (SURF1) to produce brain organoids.…”
Section: Cutting-edge Technologies For Genetic Modifications Of Ipscs...mentioning
confidence: 99%
“…Exploring Gene Therapy: Investigate the feasibility of gene therapy as a therapeutic approach for Chiari malformation and syringomyelia. Cutting-edge gene-editing tools like CRISPR/Cas9 present novel avenues for rectifying genetic mutations that cause diseases [80].…”
Section: Gene Expression Analysismentioning
confidence: 99%